Los plaguicidas utilizados en las haciendas bananeras la Iberia del cantón el Guabo y la Iberia del cantón Machala, provincia de El Oro y su impacto ambiental en el recurso suelo y los posibles riesgos en la salud de los trabajadores año 2014. - Cedeño García, Martha Margarita (2015)
This thesis is developed in the banana plantations The El Guabo Canton Iberia and Iberia Machala Canton where the activity is clearly banana. The main problem of the banana industry is the bad management and poor use of pesticides to control various pests that attack the banana production, this has caused environmental damage and soil resources where the product is applied directly.